Pengaruh Pertumbuhan Penduduk Terhadap Tingkat Pengangguran di Indonesia - Azhar Apriandi; Amrani Amrani; Fauzi Fauzi (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2026)
This study aims to analyze the effect of population growth on the unemployment rate in Indonesia. High population growth without being accompanied by an expansion of employment opportunities is one of the contributing factors to the high unemployment rate. The study employs a quantitative approach using secondary data sourced from the Central Bureau of Statistics (BPS) for the period 2015–2023. The data analysis technique applied is multiple linear regression with a panel data model. The results indicate that population growth has a positive and significant effect on the unemployment rate in Indonesia. This finding suggests that every increase in population will raise the number of labor force participants, which in turn leads to higher unemployment if available job opportunities are insufficient. The study provides a theoretical contribution to strengthening population and employment theories, as well as policy recommendations for the government to control the rate of population growth and create productive employment opportunities.